Pengaruh Kompetensi dan Motivasi terhadap Kinerja Anggota Reskrim Polres Blitar Kota dalam Pengamanan Pemilihan Gubernur Jawa Timur Tahun 2018 - Earlyanti, Novi Indah; Ardiansyah, Dhany (Journal of Management and Business Review, 2021)
Blitar Police Station is one of the jurisdictions in East Java Province which has participated in securing the Governor's Election in 2018. Security is carried out in terms of managerial human resources, by minimizing the potential of existing security disturbances soas not to develop into real disturbances.The research objective was to analyze the effect of competence and motivation on the performance of members of the Blitar City Police Criminal Investigation Unit in securing the East Java Governor Election in 2018. Quantitative research approaches and survey methods. Data obtained from filling out questionnaires of 56 items by 73 respondents who were sampled. From the results of the analysis obtained a regression equation is Y = 15,028+0,250X1+0,313X2+e ; It was concluded that the competency variable was 0.250 and motivation was 0.313 with a significant value of 0.005 and 0,000 which partially affected the performance of members. Simultaneously, the variables of competence and motivation affect performance by 34.4%. Members can produce good performance if there is support for self-competence and motivation that is formed. This is inseparable from the role of the leader who gives members the opportunity to take part in training education, gives responsibility, maintains positive interactions so as to generate motivation that can spur members to complete predetermined work targets to produce good performance.